Aspergillus niger inulinase immobilized in polyurethane foam and treated in pressurized LPG: A potential catalyst for enzymatic synthesis of fructooligosaccharides. Issue 6 (1st November 2016) - Kuhn, Graciele de Oliveira; Silva, Marceli Fernandes; Mulinari, Jéssica; Golunski, Simone; Dallago, Rogério Marcos; Dalla Rosa, Clarissa; Valério, Alexsandra; Oliveira, Débora de; Oliveira, J. Vladimir; Mossi, Altemir José; Treichel, Helen
Abstract: Inulinase from Aspergillus niger was immobilized in polyurethane foam (PU). Immobilized catalyst was treated in pressurized liquefied petroleum gas (LPG) system. This biocatalyst was used in the fructooligosaccharide production using sucrose as substrate in aqueous system. The main objective of this study was to evaluate the reaction yield and productivity by using polyurethane foam as a low-cost support for enzyme immobilization in an alternative processes for fructooligosaccharide production in pressurized LPG system with potential for industrial application. The total FOS concentration obtained were 31% as a result of sucrose concentration reduction, and formation of FOS long chain (GF3 and GF4) from kestose (GF2). FOS concentrations of 5%, 22%, and 3% were obtained for GF2, GF3, and GF4, respectively. The methodology suggested in this research work, enzyme immobilization in a low-cost support, and treatment in LPG, showed potential technology for fructooligosaccharide synthesis.